Influence of texture and grain misorientation on the ionic conduction in multilayered solid electrolytes – interface strain effects in competition with blocking grain boundaries. Issue 14 (21st March 2018) - Keppner, J.; Schubert, J.; Ziegner, M.; Mogwitz, B.; Janek, J.; Korte, C.
Abstract : We investigate the relaxation of mismatch induced interface strain as a function of the texture and its influence on the ionic conductivity in YSZ/Er2 O3 multilayer thin films. Abstract : Interface strain and its influence on the ionic transport along hetero-interfaces has gained a lot of attention over the last decade and is controversially discussed. We investigate the relaxation of mismatch induced interfacial strain as a function of the degree of orientation/texture of the columnar crystallites and assess the impact on the oxygen ion conductivity in Er2 O3 /YSZ multilayer systems. Results from X-ray diffraction clearly show, that the width of the strained hetero-interface region increases with an increasing degree of orientation of the crystallites. The combined impact of film texture and strain at the hetero-interfaces of the film on the ionic conductivity however is not easily deduced from these measurements. The samples with the highest degree of orientation, i.e. with only one azimuthal variant, show strong anisotropic electrical properties. In samples with a lower degree of orientation, i.e. samples with a fiber texture, anisotropic properties cannot be detected, possibly due to a geometrical averaging of the electrical properties. The expected strain induced monotonic increase of the ionic conductivity with decreasing layer thickness and thus increasing interfacial influence could only be detected for samples with a fiber texture and a considerable degree of crystallite misorientation. This leads to the important conclusion that the texture and therefore the nature of the grain boundaries and their network influence the ionic conductivity of the multilayer thin films in the same order of magnitude as the misfit induced interface strain. Thus, the potential design of strain-controlled ionic conductors requires additionally the control of the microstructure in terms of grain orientation.